2002
DOI: 10.1101/gr.196101
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Genomic Analysis of Two Distant Diptera, the Fruit Fly, Drosophila melanogaster, and the Malaria Mosquito, Anopheles gambiae

Abstract: Genome evolution entails changes in the DNA sequence of genes and intergenic regions, changes in gene numbers, and also changes in gene order along the chromosomes. Genes are reshuffled by chromosomal rearrangements such as deletions/insertions, inversions, translocations, and transpositions. Here we report a comparative study of genome organization in the main African malaria vector, Anopheles gambiae, relative to the recently determined sequence of the Drosophila melanogaster genome. The ancestral lines of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 55 publications
2
43
0
Order By: Relevance
“…The degree of shared synteny among representatives of the Lepidoptera, currently all within the infraorder Heteroneura (diverged B160 Myr ago; Labandeira et al, 1994), is comparable to that found within the single, 65-Myr-old genus Drosophila (Singh et al, 2009). By comparison, the genomes of two distantly related dipterans, Anopheles gambiae and Drosophila melanogaster, have been extensively reshuffled during 250 Myr of divergence (Bolshakov et al, 2002). The chromosome scale patterns in Lepidoptera may mask higher rates of gene order rearrangement at the finest scale (that is, neighboring genes), as revealed by interspecific comparisons of contiguous sequence (d 'Alenc¸on et al, 2010;Conceic¸ão et al, 2011), possibly associated with holocentrism and transposable elements.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of shared synteny among representatives of the Lepidoptera, currently all within the infraorder Heteroneura (diverged B160 Myr ago; Labandeira et al, 1994), is comparable to that found within the single, 65-Myr-old genus Drosophila (Singh et al, 2009). By comparison, the genomes of two distantly related dipterans, Anopheles gambiae and Drosophila melanogaster, have been extensively reshuffled during 250 Myr of divergence (Bolshakov et al, 2002). The chromosome scale patterns in Lepidoptera may mask higher rates of gene order rearrangement at the finest scale (that is, neighboring genes), as revealed by interspecific comparisons of contiguous sequence (d 'Alenc¸on et al, 2010;Conceic¸ão et al, 2011), possibly associated with holocentrism and transposable elements.…”
Section: Discussionmentioning
confidence: 99%
“…Complete genome sequencing of both D. melanogaster and A. gambiae allowed the identification and analysis of NTs in two different species of Diptera, which are thought to have diverged ϳ250 million yr ago (9). About half of the genes in these arthropods are thought to be orthologs with an average of ϳ56% sequence identity (32).…”
Section: Discussionmentioning
confidence: 99%
“…This means that Drosophila tubules provide a useful model for those of major medical and agricultural pests, such as mosquitoes and tsetse flies, in advance of any transgenic technologies that may be developed for their detailed study later. They can thus act as a proxy for species like Anopheles gambiae with a recently completed genome (27), but technically challenging transgenesis (10). This is discussed in section XIIIB.…”
Section: G Insect Tubules As Targets For Selective Insecticidesmentioning
confidence: 99%